Environmental Education in Junior High School Science: Teachers’ Integration Perceptions through Distance Learning Modality - Punzalan, Christopher (Universitas Negeri Semarang, 2024)
In the educational paradigm, it is crucial to consider how education can address the significant environmental and biodiversity changes causing exponential degradation, particularly during the pandemic. This study analyzed junior high school science teachers’ perceptions of integrating environmental education (EE) into the curriculum through online distance learning. This research method used survey and case study designs involving thirty-two science teachers from eight schools in Cavite, Philippines. Quantitative data analysis revealed that science teachers incorporated EE during the pandemic. Additionally, qualitative data analysis identified several themes related to science teachers’ perceptions: 1) impressions and understanding of EE, 2) benefits of integrating EE into science, and 3) balancing the values and drawbacks. In conclusion, most science teachers agreed with statements regarding their strategies for integrating EE into the science curriculum. Critical issues regarding science teachers’ attitudes toward EE integration were identified through interviews and focus groups. This demonstrates how educational technology, mainly when used with remote learning, may facilitate and improve the integration of EE into science instruction. This study offers workable answers for converting these concepts into ecological activities and successful methods for incorporating EE into junior high school science curricula.